Intercultural pastoral care and counseling: resources from narrative therapy and brief pastoral counseling - Müller, J. C. (Verbum et ecclesia, 1998)
The fascinating, but complex field of intercultural communication and pastoral care is the focus of research in this article. The authors describe the two approaches of pastoral therapy and show how it can be implemented in an intercultural setting. Although there are major differences between the narrative and brief counseUng approaches, there are also striking similarities. In both cases the pastor tries to work from a nonexpert position and is non-prescriptive in the approach. The authors are convinced that this basic approach of respectfulness makes both models usefull for intercultural work.